Socio-economic, technological and environmental drivers of spatio-temporal changes in fishing pressure. (February 2018) - Stephenson, Fabrice; Mill, Aileen C.; Scott, Catherine L.; Stewart, Gavin B.; Grainger, Matthew J.; Polunin, Nicholas V.C.; Fitzsimmons, Clare
Abstract: As part of an ecosystem based approach to fisheries management (EBFM), the heterogeneity of biological communities, key ecological processes and human uses must be understood. Although fishing effort distribution and marine habitat distribution and use are increasingly well understood, little research has quantified spatio-temporal changes in fishing effort or investigated drivers of these changes. Here, a holistic approach was taken to investigate socio-economic, environmental and technological drivers of change in fishing effort distribution of the Northumberland pot-fishery (2004–2014) using Bayesian Belief Network (BBN) analyses. BBNs were populated using large-scale high resolution spatial and temporal fisheries monitoring data, quantitative and qualitative interviews with fishers and expert opinion. Increases in fishing effort over time were explained by a combination of changes in fleet composition and fishers' behaviour. Increasing vessel and engine sizes, combined with an increased uptake of improved fishing technology have resulted in a greater ability for vessels to fish a greater number of pots. This increase in vessel and fishing capability has resulted in fishers' increased ability to fish in harsher weather conditions, as well as target specific areas or habitats quickly and opportunistically. Non-technological factors, such as declines in stocks of finfish and nephrops and the increasing operational costs of participating in these fisheries may have resulted in fishers solely fishing in the less regulated pot-fishery, targeting high value European lobster on a full-time basis. Increasing costs of pot-fishing in Northumberland coupled with stagnating crab and lobster landings prices may have resulted in increased fishing effort to maintain profitability. Highlights: Large social-ecological datasets analysed in flexible BBN decision models. Investigation of drivers of spatial and temporal changes in fishing effort. Analysis includes often overlooked socio-ecological drivers for fisheries management. Flexible BBN modelling allows possible fisheries management scenarios to be explored.